2018
DOI: 10.1097/hjh.0000000000001602
|View full text |Cite
|
Sign up to set email alerts
|

Association of retinal vessel calibers and longitudinal changes in arterial stiffness

Abstract: Narrower CRAE in middle-age was associated with the long-term risk of arteriosclerosis in a general population sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Given that almost all the included studies were cross‐sectional, we were unable to explore the temporal directions of the observed associations. The only longitudinal study, which followed an adult population over five years, suggested that narrower retinal arteriolar caliber was an independent predictor of increased PWV . Longitudinal replication in other cohorts is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that almost all the included studies were cross‐sectional, we were unable to explore the temporal directions of the observed associations. The only longitudinal study, which followed an adult population over five years, suggested that narrower retinal arteriolar caliber was an independent predictor of increased PWV . Longitudinal replication in other cohorts is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The only longitudinal study, which followed an adult population over five years, suggested that narrower retinal arteriolar caliber was an independent predictor of increased PWV. 43 Longitudinal replication in other cohorts is warranted. Participants were mainly middle-or older-aged adults, limiting conclusions that could be drawn for younger stages of the life course.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Nonmydriatic retinal photography allows noninvasive visualization of the retinal microvasculature in population surveys. 1719 Few studies addressed the association between the retinal microcirculation and the properties of the large arteries 2024 but are difficult to interpret, because they cannot be generalized to the general population, 21,23 because they involved brachial-ankle PWV and thereby encompassed both elastic and muscular arteries, 22,24 or because they had a small sample size. 21,23 Our literature review did not reveal any previous study that addressed the possible association of retinal microvascular traits with the forward and backward components of the aortic pulse wave.…”
mentioning
confidence: 99%
“…21,23 Our literature review did not reveal any previous study that addressed the possible association of retinal microvascular traits with the forward and backward components of the aortic pulse wave. 2024 We addressed this knowledge gap by analyzing data from the FLEMENGHO (Flemish Study on Environment, Genes, and Health Outcomes). 25…”
mentioning
confidence: 99%